Intersectionality in Digital Humanities - Bordalejo, Barbara; Risam, Roopika (Collection Development, Cultural Heritage, and Digital Humanities, 2019)
Coined by Kimberlé Crenshaw in the late 1980s, intersectionality makes the case that dimensions of identity, such as gender and race, cannot be understood in isolation from each other because they work together to shape lived experience. As digital humanities has expanded in scope and content, questions of how to negotiate the overlapping influences of race, class, gender, sexuality, nation, and other dimensions that shape data, archives, and methodologies have come to the fore. Taking up these concerns, the authors in this volume explore their effects on the methodological, political, and ethical practices of digital humanities. Essays examine intersectionality from a range of positions: the influence of overlapping identities on scholars within the digital humanities community; how the fields in which they work are subject to competing tensions created by intersecting power structures within digital humanities and academia; and the methodological possibilities and scholarly potential for intersectionality as a framing theory in digital humanities scholarship.